2003
DOI: 10.1152/japplphysiol.00777.2002
|View full text |Cite
|
Sign up to set email alerts
|

Serial changes in nasal potential difference and lung electrical impedance tomography at high altitude

Abstract: Mason, Nicholas P., Merete Petersen, Christian Mé lot, Bakyt Imanow, Olga Matveykine, Marie-Therese Gautier, Akpay Sarybaev, Almaz Aldashev, Mirsaid M. Mirrakhimov, Brian H. Brown, Andrew D. Leathard, and Robert Naeije. Serial changes in nasal potential difference and lung electrical impedance tomography at high altitude. J Appl Physiol 94: 2043-2050, 2003. First published December 6, 2002 10.1152 10. /japplphysiol.00777.2002 work suggests that treatment with inhaled ␤2-agonists reduces the incidence of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
23
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 46 publications
10
23
2
Order By: Relevance
“…This is in keeping with previous hemodynamic and echocardiographic measurements, indicating an enhanced LV systolic function in hypoxic healthy volunteers (2,6,19,24,29). In contrast, hypoxia did not affect RV area SF, TAPSE, nor any of the pulsed TDI indexes of systolic RV function, all of which were increased by dobutamine.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in keeping with previous hemodynamic and echocardiographic measurements, indicating an enhanced LV systolic function in hypoxic healthy volunteers (2,6,19,24,29). In contrast, hypoxia did not affect RV area SF, TAPSE, nor any of the pulsed TDI indexes of systolic RV function, all of which were increased by dobutamine.…”
Section: Discussionsupporting
confidence: 91%
“…keeping with previous reports of hypoxic exposure-induced LV diastolic dysfunction on the basis of transmitral flow (2,6,19) and recently of mitral annulus pulsed TDI increased A wave in high-altitude newcomers (2). The authors of this last study suggested that increased atrial contraction may prevent the appearance of LV diastolic dysfunction in healthy subjects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Two recent studies reported an altitude-induced increase in nasal PD in healthy subjects [34,35]. This finding, which is in contrast with the current data and all the available in vitro and in vivo data on the effects of hypoxia on respiratory sodium transport [5,15], has been attributed to nasal epithelial dryness-induced increase in chloride secretion [35], a phenomenon that has never been shown to occur at the alveolar level.…”
Section: Discussioncontrasting
confidence: 89%